The Role of Risk Tolerance in Moderating Financial Literacy and Fintech on Green Investment Intention - Puspita Azura Diva Rachmalia; Suhita Whini Setyahuni; Dwi Eko Waluyo; Dian Prawitasari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of Financial Literacy and Fintech utilization on Green Investment Intention, as well as to examine the role of Risk Tolerance as a moderating variable among the general public in Indonesia. The study uses a quantitative approach with an online survey of 150 respondents aged at least 18 years who have access to digital financial services and an interest in sustainable investment, using purposive sampling. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results show that Financial Literacy and the use of Fintech have a positive effect on Green Investment Intention, while Risk Tolerance has a direct effect and strengthens the relationship between Financial Literacy and Fintech with Green Investment Intention. The research model was able to explain 70.2% of the variation in Green Investment Intention, confirming the importance of cognitive, technological, and psychological factors in encouraging sustainable investment. The novelty of this research lies in the integration of financial literacy, Fintech, and Risk Tolerance as moderating variables in the sustainable financial behavior model among the general public in Indonesia. These findings contribute to the development of sustainable finance literature and provide practical implications for governments, financial institutions, and Fintech providers in designing financial education policies and digital services that support the transition to a green economy.